An integral approach to the study of bromalites. Late Quaternary and neo-taphonomic case studies from arid South America - Mariana Mondini (Quaternary Science Advances, 2023)
Bromalites are fossil traces of organisms, consisting of material from their digestive system, including coprolites, regurgitalites, consumulites, pabulites and digestilites (Hunt, 1992; Hunt and Lucas, 2021). As such, they inform about the interactions between bromalite-producing organisms and others, as well as between them and the environment generally, at a relatively fine temporal and spatial resolution. Yet, bromalites have often been dismissed in paleontological and, especially, archaeological research. This work discusses the relevance of bromalites as sources of paleoecological and even cultural information, and the importance of integrating multiple lines of evidence and different scales of analysis in the taphonomic study of bromalites. To do so, it reviews the different proxies that can be analysed, and illustrates this integral approach with examples of late Quaternary and modern contexts from an ongoing project in arid South America. It intends to show the potential of such a multiproxy and multiscale approach in order to elicit as much information as possible from these palaeobiological reservoirs.